Ultra-Processed Food Consumption Is Associated With Poor Diet Quality and Nutrient Intake Among Adolescents in Urban Slums, Kenya - Milkah N. Wanjohi; Milkah N. Wanjohi; Gershim Asiki; Calistus Wilunda; Michelle Holdsworth; Rebecca Pradeilles; Linda Simon Paulo; Linda Simon Paulo; Nelson Langat; Dickson A. Amugsi; Simon Kimenju; Elizabeth W. Kimani-Murage; et al. (International Journal of Public Health)
ObjectivesTo assess the caloric contribution of ultra-processed foods (UPFs), factors associated with UPFs energy intake and investigate the relationship between UPFs energy intake, diet quality and nutrient intake among adolescents in urban slums, Kenya.MethodsA cross-sectional household study amongst adolescents (10–19 years, N = 621) collected socio-demographic and dietary intake data. Global Diet Quality Score (GDQS); mean and percentage total energy intake (%TEI) from UPFs; and nutrient intakes were computed. Regression analysis assessed the factors associated with UPFs energy intake, and the association between %TEI from UPFs and diet quality.ResultsMean daily energy intake was 1,604 kcal (±550), 25.2% from UPFs. Higher leisure screen time (≥2 h/day) [OR = 1.9 (1.2–3.1)] was associated with UPFs energy intake. Household wealth index (quintile five vs. one) [OR = 2.6 (1.3–6.0)] was associated with non-UPFs energy intake. UPFs (%TEI) was inversely associated with GDQS score (quartile four vs. one) [β = −2.9 (−3.4 to −2.1)]. Adolescents with higher %TEI from UPFs (quartile four) had highest total energy, total fat and saturated fat; and lowest protein, fibre, iron, calcium and zinc intake.ConclusionUPFs contribute substantially to adolescents’ energy intake and are linked to poor diet quality and nutrient intake.